EVALUATION OF DESIGN PRINCIPLES FOR BABYLON PARK - & Jasim, Al-Bawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Attention Recently directed to the importance of urban parks and gardens, being one of the basic and essential components to develop quality of urban life. The evaluation of design characteristics of the historical landscape parks from different aspects, one of the most important goals aspires landscape designer to be studied within the master plan of the city. The search adopted field survey methodology and observation, description within limits of current study. Babylon park using the camera and recording videos, in order to embody the components and elements of the overall site, using aerial maps of park site to sketching the sites accurately ,taking into consideration relationship of study area to neighboring areas. Evaluation process of Babylon Tourist Park included four main stages the obtain information,analysis characteristic features, determine the importance and integrity of the site), were also distributed evaluation form on a sample of experience in the planning,design and plants persons responsible for the management and maintenance of the park. After Data were processed using Microsoft office excel 2010. To find duplicates and percentages for evaluators answers. The results for the evaluation for the artificial components (the main gate,the main buildings,the roads and the lanes) were appropriate for the site ,mean while the car park was unsuitable in terms of design aesthetic and functionality regarding the natural components. The effectiveness of the observation of nature got the highest evaluation, followed by recreational travel and the and finally holding concerts and confirmed the importance of evaluating the results of the park and all the interlocutor where you got the utmost preference as a public garden combines with view of natural and historical properties. Vegetation has been characterized by large trees with great differences in the kind and tissue of the tree , while the shrubs was a great contrast to the average in terms of forms and spun.It turns out that Babylon tourist park is one of the most important natural parks - historical, which is located in the city of Hilla, center, and increasingly important compared with the gardens of other city because it is one of the elements of the powerful attractions of the city culturally and historically as a result of his involvement in important historical events as well as it relates to environmental and natural monuments.